Gender differences in body composition, dietary patterns, and physical activity: insights from a cross-sectional study - Lombardo, Mauro; Feraco, Alessandra; Armani, Andrea; Camajani, Elisabetta; Gorini, Stefania; Strollo, Rocky; Padua, Elvira; Caprio, Massimiliano; Bellia, Alfonso (Frontiers in Nutrition, 2024)
This study examines the interactions between body composition, dietary pa erns, and physical activity across genders, highlighting significant gender-specific differences in food preferences and eating behaviours. In this cross-sectional study of 1333 individuals (58.7% female, 41.3% male), aged between 18 and 65 years, we explored the interactions of body composition and gender on dietary choices, eating behaviour, and physical activity. Participants were categorised into tertiles based on their fat mass to fat-free mass (FM-to-FFM) ratio, revealing significant gender-specific differences in food preferences and eating behaviours. Perception of hunger varies by time of day between genders, with males experiencing greater hunger in the late afternoon and females in the morning. Food preferences also differ significantly between FM-to-FFM tertiles and gender, with males showing a greater preference for processed meats and red meat and females for cooked vegetables. Skipped meal pa erns, uncontrolled eating behaviour, nocturnal eating habits and taste preferences (sweet or salty) show distinct trends between FM-to-FFM tertiles and between genders. Furthermore, sports participation pa erns reveal a correlation between higher FM-to-FFM ratios and lower activity levels, particularly in strength training and general sports engagement. These findings underline the complex interaction between body composition, dietary habits and lifestyle factors, highlighting gender-specific differences and the impact of BMI on health-related behaviours.